1999
DOI: 10.1074/jbc.274.39.27891
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Thioredoxin in the Cytoplasm and in the Nucleus

Abstract: Oxidative stresses such as UV irradiation to mammalian cells triggers a variety of oxistress responses including activation of transcription factors. Recently, activation of nuclear factor-B (NF-B) has been shown to be under oxidoreduction (redox) regulation controlled by thioredoxin (TRX), which is one of major endogenous redox-regulating molecules with thiol reducing activity. In order to elucidate where in the cellular compartment TRX participates in NF-B regulation, we investigated the intracellular locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
165
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 525 publications
(173 citation statements)
references
References 64 publications
6
165
2
Order By: Relevance
“…The role of TRX in the regulation of AP-1 DNAbinding activity following IR, as well as other environmental stress inducing agents (Hirota et al, 1999(Hirota et al, , 2000a, has been well established. However, the role of the critical cysteines in IR-induced induction of the AP-1 complex has not been investigated.…”
Section: Characterization Of Trx and Tr Overexpressing Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of TRX in the regulation of AP-1 DNAbinding activity following IR, as well as other environmental stress inducing agents (Hirota et al, 1999(Hirota et al, , 2000a, has been well established. However, the role of the critical cysteines in IR-induced induction of the AP-1 complex has not been investigated.…”
Section: Characterization Of Trx and Tr Overexpressing Cell Linesmentioning
confidence: 99%
“…It has been previously shown that following exposure to IR (Wei et al, 2000) or other oxidants (Hirota et al, 1999(Hirota et al, , 2000a, TRX translocates into the nucleus, where it interacts with another redox-sensitive signaling protein, redox factor-1, and appears to regulate the nuclear transcription factor complex, AP-1. The current study demonstrates the essential role of TR as a redox-sensitive signaling factor functioning upstream of TRX in the regulation of AP-1 activity and demonstrates that the active site cysteine residues are essential in mediating IR-induced activation as well as the regulation of stress-induced TRX nuclear translocation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During oxidative stress conditions IkBa becomes ubiquitinylated and subsequently degraded by the 26S proteasome complex. It was shown that Trx inhibits the degradation of IkBa (Hirota et al, 1999). We demonstrate here that Trx also induces the expression of IkBa/MAD-3.…”
Section: Discussionmentioning
confidence: 50%